Pelatihan Geogebra: Pemodelan Matematika Menggunakan Kalkulus - Meryani Lakapu; Aloysius Joakim Fernandez; Irmina Veronika Uskono; Yohanes Ovaritus Jagom; Wilfridus Beda Nuba Dosianaeng (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
During the COVID-19 pandemic, everyone has the free opportunity to learn various things and anywhere. Therefore, this service activity provides breadth for all mathematics students/teachers/lecturers in Indonesia to learn about Mathematical Modeling using Calculus, which is assisted by the GeoGebra application. This activity is a collaboration between the Indonesian Mathematical Association (IndoMs), Program Studi Pendidikan Matematika Sanata Dharma, Program Studi Matematika Universitas Kristen Satya Wacana dan Program Studi Pendidikan Matematika Universitas Katolik Widya Mandira. Participants in this activity amounted to 62 (students, teachers and lecturers) from 15 campuses and 5 high schools spread throughout Indonesia. The objectives of this training are for participants to be able to: (1) understand the basic concepts of modeling using calculus; (2) pose everyday problems that can be modeled with calculus; (3) able to use geogebra in completing and analyzing mathematical modeling; and (4) able to communicate the results of mathematical modeling in written and oral form in a structured manner. Based on the evaluation results, this activity can be carried out well and the expected goals can be achieved.